Pelaksanaan Evaluasi dan Pengembangan Konsep KurikulumPendidikan Islam sebagai Rekonstruksi Sosial dan Rasionalisasi Akademik - Ade Salamun; Abuddin Nata (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine the implementation of evaluation and development of curriculum concepts as social reconstruction and academic rationalization at the Daar El Manshur Islamic Boarding School. This study also aims to determine the supporting and inhibiting factors in the implementation of the evaluation and development. This research is a field research conducted at the Daar El Manshur Islamic Boarding School with a qualitative method. Data was collected by using in-depth interviews with informants and then analyzed using content analysis. The results of the analysis show that the implementation of curriculum evaluation and development with an academic rationalization approach and social reconstruction has not run optimally because the evaluation of the curriculum implementation process does not yet have an assessment measurement tool and is only carried out in the form of reports. However, the follow-up to the evaluation can still be carried out. This can be seen from the implementation of curriculum development at the DEM Islamic Boarding School, such as the addition of a curriculum that is in accordance with the goals, vision, and mission of the pesantren. However, due to the large number of teachers who do not have an educational background, this is one of the inhibiting factors, but the ease in conveying opinions and opportunities to take higher education levels for teachers is expected to carry out the evaluation of the concept of curriculum development in the future to run optimally.